Two new species of Podostemaceae from the Yinggeling National Nature Reserve, Hainan, China - Lin, Qin-Wen; Lu, Gang; Li, Zheng-Yu (Phytotaxa, 2016)
In this paper we describe and illustrate two new species, Cladopus yinggelingensis and Terniopsis daoyinensis, both from the Yinggeling National Nature Reserve, Hainan, China. Morphologically, Cladopus yinggelingensis is similar to C. doianus, and Terniopsis daoyinensis is similar to T. ubonensis. For the new taxa, information on its geographic range, habitat, and morphological differences between their known congeneric species are presented.